Demographic Characteristics and Reproductive Profile of Pregnant Women in Jamnagar District - Sumit V Unadkat; Sudha Yadav; J P Mehta; Dipesh V Parmar; Kishor M Dhaduk (Medsci Publications, 2013)
Introduction: Many of the health problems of Indian women are related to or exacerbated by high levels of fertility. The poor health of Indian women is a concern on both national and individual levels. It affects the children who will be India's next generations of citizens and workers. The current study was aimed to see the impact of demographic characteristics on reproductive profile of pregnant women. Material and Methods: It was a community based cross-sectional study conducted among 300 pregnant women using pretested questionnaire. Sample size was calculated using the proportion of pregnant women having one or more living children. Results: Out of total 300 pregnant women studied, 6.00% of the total studied women were adolescents. Study revealed that 34.67% of the pregnant women were illiterate. More than three fourth i.e. 78.33% of the studied women got married by the age of 21 years and 16 % got married before legal age of marriage. Considering the age at first conception, 59 % women of the study group had their first pregnancy by 21 years of age and 5.00% of the study women conceived for the first time before 18 years of age. For 27.33% of the studied women, it was their third or more conception, while 17.33% of the studied pregnant women had two or more live children. Conclusion: Study revealed significant impact of area of residence, literacy of the women and socio-economic class of the family over reproductive profile of women including interpregnancy interval and high parity.